Treatment of a Deep Bite Malocclusion with Extraction and Bite-Fixer - Müge Aksu; Derya Germeç; Tülin Uğur-Taner (Galenos Yayinevi, 2008)
This case report presents the treatment of a deep-bite malocclusion by premolar extraction and Bite-fixer appliance. A 13-year-old female patient concerned about the appearance of her crooked upper teeth. Her facial appearance revealed a retrusive profile. The crowding in maxillary and mandibular arches were, 15 mm and 9.5 mm respectively. Intraoral examination showed that the buccal segments were in full Class II relationship. Upper canines were highly positioned and there was a deep overbite. The cephalometric analysis demonstrated the Class II mandibular retrusion. Upper and lower incisors were also retroclined and both upper and lower lips were in retrusion. To relieve crowding, upper first and lower second premolars were extracted, then upper and lower incisor angulations were corrected and the mandibular dentoalveolar region was advanced by a Bite-Fixer appliance. At the end of the treatment, Class I molar and canine relationships were achieved, the crowding was eliminated, deep-bite was corrected and the lower incisors were proclined. The patient's profile was also improved. This case showed that extraction treatment could be a good alternative even in Class II deep bite cases when a fixed functional appliance was used.